2022
DOI: 10.1021/acs.jmedchem.1c02058
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and Structural Optimization of Toddacoumalone Derivatives as Novel PDE4 Inhibitors for the Topical Treatment of Psoriasis

Abstract: Psoriasis is a common immune-mediated skin disorder manifesting in abnormal skin plaques, and phosphodiesterase 4 (PDE4) is an effective target for the treatment of inflammatory diseases such as psoriasis. Toddacoumalone is a natural PDE4 inhibitor with moderate potency and imperfect drug-like properties. To discover novel and potent PDE4 inhibitors with considerable druggability, a series of toddacoumalone derivatives were designed and synthesized, leading to the compound (2R,4S)-6-ethyl-2-(2-hydroxyethyl)-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…To maintain its binding mode in PDE4, we adopted another optimization strategy: cleavage of the tetrahydro-2 H -pyran-4-yl group to chain substituents encompassing a terminal hydrophilic group (Table ). In addition, it has been confirmed that introducing hydrophilic groups (such as OH and COOH) into the end of the side chain is conducive to their binding to the metal region in the active cavity. In a manner akin to the ring-opening procedure of ZL6 , substitutions at N 1 or N 2 of 5-azaindazole were replaced by a length alkyl chain with 1–4 carbon atoms encompassing a terminal hydrophilic group, such as OH, COOH, and CONHOH.…”
Section: Resultsmentioning
confidence: 96%
“…To maintain its binding mode in PDE4, we adopted another optimization strategy: cleavage of the tetrahydro-2 H -pyran-4-yl group to chain substituents encompassing a terminal hydrophilic group (Table ). In addition, it has been confirmed that introducing hydrophilic groups (such as OH and COOH) into the end of the side chain is conducive to their binding to the metal region in the active cavity. In a manner akin to the ring-opening procedure of ZL6 , substitutions at N 1 or N 2 of 5-azaindazole were replaced by a length alkyl chain with 1–4 carbon atoms encompassing a terminal hydrophilic group, such as OH, COOH, and CONHOH.…”
Section: Resultsmentioning
confidence: 96%
“…[20] The compound featured a naphthyridine scaffold and showed moderate potency as PDE4I, with the IC 50 value of 400 nM. The TCD2 bioactive conformation within the PDE4D catalytic site has been elucidated by X-ray crystallography (PDB code = 7W4X), [24] opening the possibility to proceed with the rational design of the further new analogues (see chemical structures in Supporting Information Table S3).…”
Section: Exploring In Silico Naphthyridine (Tcds) As Pde4 Inhibitorsmentioning
confidence: 99%
“…According to statistics by 2019, natural products as well as their derivatives accounted for 49.2% of the drugs approved by FDA, indicating that natural products are an invaluable source for the identification of lead compounds and pharmacophores . Many natural product derivatives were also discovered as effective PDE4 inhibitors. In recent years, we have been engaged in the exploration of anti-inflammatory active ingredients from TCM, such as Magnolia biondii Pamp, Scrophularia ningpoensis Hemsl., Scrophularia dentata Royle ex Benth., Eriobotrya japonica (Thunb. )­Lindl., and so forth.…”
Section: Introductionmentioning
confidence: 99%